Posttraumatic Overmodulation, Callous–Unemotional Traits, and Offending Among Justice-Involved Youth. Issue 7 (9th August 2018) - Mozley, Michaela M.; Lin, Betty; Kerig, Patricia K.
ABSTRACT: A large body of research has demonstrated an association between childhood trauma exposure (TE) and adolescent delinquency. This association may be explained by callous–unemotional (CU) traits, which may stem from TE and are associated with persistent offending and recidivism. However, research on the mechanisms underlying TE and delinquency has lacked specificity regarding the posttraumatic symptoms that may drive this effect, particularly new models that distinguish between posttraumatic symptoms (PTS) of overmodulation versus undermodulation. This article sought to investigate the role of overmodulation in the association between TE and CU traits and their relations with persistent offending. Participants included 829 detained youth who completed self-report measures of TE, PTS, and CU traits. Official records of youth offenses were also obtained. Results of path analyses demonstrated that the association between interpersonal TE and persistent offending exhibited an indirect effect through overmodulation and CU traits. Efforts to address overmodulation among traumatized detained youth may represent a promising avenue of intervention for reducing recidivism.